Patterns and predictors of relapse following radical chemoradiation therapy delivered using intensity modulated radiation therapy with a simultaneous integrated boost in anal squamous cell carcinoma - Shakir, R; Adams, R; Cooper, R; Downing, A; Geh, I; Gilbert, D; Jacobs, C; Jones, C; Lorimer, C; Namelo, W; Sebag-Montefiore, D; Shaw, P; et al. (Elsevier, 2019)
Purpose Our purpose was to describe the patterns and predictors of treatment failure in patients receiving definitive chemoradiation therapy (CRT) for anal squamous cell carcinoma (ASCC), delivered using intensity modulated radiation therapy (IMRT). Methods and Materials Our study was a retrospective cohort analysis of consecutive patients treated with curative intent for ASCC using CRT delivered with a standardized IMRT technique in 5 UK cancer centers. Patients were included from the start of UK IMRT guidance from February 2013 to October 31, 2017. Collected data included baseline demographics, treatment details, tumor control, sites of relapse, and overall survival. Statistical analysis to calculate outcomes and predictive factors for outcome measures were performed using SPSS and R. Results The medical records of 385 consecutive patients were analyzed. Median follow-up was 24.0 months. Within 6 months of completing CRT, 86.7% of patients achieved a complete response. Three-year disease-free survival and overall survival were 75.6% and 85.6%, respectively. Of all relapses, 83.4% occurred at the site of primary disease. There were 2 isolated relapses in regional nodes not involved at outset. Predictive factors for cancer recurrence included male sex, high N-stage, and failure to complete radiation therapy as planned. Conclusions The treatment results compare favorably to published outcomes from similar cohorts using 3-dimensional conformal CRT. The observed patterns of failure support the current UK IMRT voluming guidelines and dose levels, highlighting our prophylactic nodal dose as sufficient to prevent isolated regional relapse in uninvolved nodes. Further investigation of strategies to optimize CR should remain a priority in ASCC because the site of primary disease remains the overwhelming site of relapse.